Basic Elements of Equipment Cleaning and Sanitizing in Food Processing and Handling Operations - Ronald H. Schmidt (EDIS)
This document explains the procedures for cleaning and sanitizing equipment in food-processing and handling operations. It emphasizes the importance of proper cleaning to remove food residues and prevent bacterial growth. The article details various cleaning methods, including mechanical, manual, and clean-out-of-place techniques, and discusses the types of soils and appropriate detergents for their removal. It also covers the use of thermal and chemical sanitizers, highlighting factors that affect their effectiveness. The document aims to ensure food safety by providing comprehensive guidelines for maintaining clean and sanitized equipment. Original publication date July 1997.